Magnolol inhibits growth of gallbladder cancer cells through the p53 pathway. Issue 10 (October 2015) - Li, Maolan; Zhang, Fei; Wang, Xu'an; Wu, Xiangsong; Zhang, Bingtai; Zhang, Ning; Wu, Wenguang; Wang, Zheng; Weng, Hao; Liu, Shibo; Gao, Guofeng; Mu, Jiasheng; et al.
Abstract : Magnolol, the major active compound found in Magnolia officinalis has a wide range of clinical applications due to its anti‐inflammation and anti‐oxidation effects. This study investigated the effects of magnolol on the growth of human gallbladder carcinoma (GBC) cell lines. The results indicated that magnolol could significantly inhibit the growth of GBC cell lines in a dose‐ and time‐dependent manner. Magnolol also blocked cell cycle progression at G0 /G1 phase and induced mitochondrial‐related apoptosis by upregulating p53 and p21 protein levels and by downregulating cyclin D1, CDC25A, and Cdk2 protein levels. When cells were pretreated with a p53 inhibitor (pifithrin‐a), followed by magnolol treatment, pifithrin‐a blocked magnolol‐induced apoptosis and G0 /G1 arrest. In vivo, magnolol suppressed tumor growth and activated the same mechanisms as were activated in vitro . In conclusion, our study is the first to report that magnolol has an inhibitory effect on the growth of GBC cells and that this compound may have potential as a novel therapeutic agent for the treatment of GBC. Abstract : This study investigated the effects of magnolol on the growth of GBC cells. The results indicated that magnolol inhibited GBC cell growth in vitro and in vivo via the p53 pathway. This work provided a rationale for Magnolol as a novel therapeutic agent for GBC.